Vibrating Floor Design For The Climate Room With Ergonomics Aspect and Safety Approach - Patradhiani, Rurry Patradhiani; Yasmin, Yasmin; Juliyanti, Lili (Publisher Cv. Inara, 2022)
Vibration as a part of the physical work environment that can have an impact on increasing work productivity and health for workers, it is necessary to study the impact of exposure to the human body. The climate room is one of the learning facilities in the Ergonomics and Work System Design Laboratory of the Industrial Engineering Study Program. However, this climate room does not have a vibration simulation yet, so it is necessary to have a vibrating floor design that can simulate vibration as part of the conditions in the work environment. In designing the vibrating floor design, the ergonomics and safety aspects are considered by using the Ergonomic Function Deployment (EFD) method where the requirement attribute is derived from the ENASE aspect. From this research, it was found that the contribution value for each of the required attributes can be determined so that the order of priorities that must be met in the design of the vibrating floor design can be determined. The highest contribution value which shows priority 1 is 3.80 users are comfortable in operating the vibrating floor, in this case the vibrating floor design is based on the user's anthropometric data. For the lowest contribution value, namely 1.42 as priority 9, the vibrating floor treatment process is easy to do so that the target specification for the vibrating floor uses iron and painted plywood. From the design of the vibrating floor based on the attributes of the needs so that it can provide a real vibration simulation like industrial conditions Keywords: Vibration floor, Ergonomic and Safety, Ergonomic Function Deployment (EFD).